2013
DOI: 10.1016/j.future.2012.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing spot price dynamics in public cloud environments

Abstract: The surge in demand for utilizing public Cloud resources has introduced many trade-offs between price, performance and recently reliability. Amazon's Spot Instances (SIs) create a competitive bidding option for the public Cloud users at lower prices without providing reliability on services. It is generally believed that SIs reduce monetary cost to the Cloud users, however it appears from the literature that their characteristics have not been explored and reported. We believe that characterization of SIs is f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(49 citation statements)
references
References 23 publications
0
44
0
Order By: Relevance
“…A reverse engineering analysis in [15] found that Amazon sets their prices at random from within a tight price interval via a dynamic hidden reserve price. A statistical analysis and modeling of Amazon spot price dynamics is in [16]. Differently from our assumption, EC2 spot instances are priced the same to all its users.…”
Section: B Comparison With the Provisioning Scheme Inmentioning
confidence: 97%
“…A reverse engineering analysis in [15] found that Amazon sets their prices at random from within a tight price interval via a dynamic hidden reserve price. A statistical analysis and modeling of Amazon spot price dynamics is in [16]. Differently from our assumption, EC2 spot instances are priced the same to all its users.…”
Section: B Comparison With the Provisioning Scheme Inmentioning
confidence: 97%
“…Some works (e.g., [13,14,28,30,31]) focus on understanding the price dynamics to generate price predictions that can be used to make cost-effective provisioning decision. Other works (e.g., [2,29,32]) focus on providing bidding strategies that are specific for spot instances.…”
Section: Related Workmentioning
confidence: 99%
“…Also, managers will find it beneficial to understand more fully how to do effective statistical modeling of spotprice cloud computing instances in public markets (Javadi et al 2011) and how spot prices change in these kinds of market environments (Javadi et al 2013). In future markets, data analytics for different kinds of cloud computing instances, and how demand and supply interact over time in the presence of managerial choices on pricing for them, will become strategic capabilities for cloud computing vendors and their clients.…”
Section: Research Directions For Cloud Computing Mechanism Designmentioning
confidence: 99%